AB0097 V667m, a1330v and n740n polymorphisms in lrp5 gene are associated with bone mineral density and bone metabolism in established rheumatoid arthritis patients. (23rd January 2014) - Bernardes, M.; Machado, J. C.; Vieira, T.; Terroso, G.; Abelha-Aleixo, J.; Madureira, P.; Vieira, R.; Fonseca, R.; Gonçalves, D.; Bernardo, A.; Pimenta, S.; Oliveira, A.; et al.
Abstract : Background: Rheumatoid arthritis (RA) is characterized by a localized bone resorption at the hands, namely, and generalized osteoporosis. LRP5 gene is related to rare metabolic bone diseases and several LRP5 polymorphisms have been associated with bone mineral density (BMD) in healthy populations. Objectives: To determine the association of three LRP5 gene polymorphisms with bone density and metabolism in patients with established rheumatoid arthritis (RA) Methods: Clinical features and peripheral blood samples were collected. The Portuguese version of HAQ, DAS28 (4v)), tender (out of 68) and swollen (out of 66) joint counts were obtained. Several laboratory parameters were measured: ESR, CRP, serum β-C-telopeptides of type 1 collagen cross-links (β-CTX1), osteocalcin, Dkk-1 (ELISA, Biomedica), sclerostin (ELISA TECOmedical), RANKL (ELISA, Cusabio) and OPG (ELISA, Biomedica). BMD was assessed by DXA (Lunar Expert ® 1320) at lumbar spine, total hip, femoral neck, Wards triangle, hands and second proximal phalanges. A multivariate analysis model was used for statistical analysis (PASW Statistics 18). Results: We evaluated 208 RA patients, 166 (80%) women, 65 (31%) premenopausal women, age 54 ± 12 years, disease duration 14 ± 10 years, mean DAS28 (4v) of 4.25 ± 1.33 and a mean HAQ of 1.254 ± 0.709. In our sample, 107 (51%) were under biologics, 87 (42%) under anti-TNFalpha agents, 69 (33%) under bisphosphonates and 42 (20%) under vitamin D supplements, Genotypic frequencies were determined: V667M (GG 89%, 11% AG, AA: 1%), N740N (CC 69%, 27% TC, TT 4%) and A1330V (CC 72% TC 24%; TT 4%). The AG genotype (V667M LRP5), the TT genotype (N740N LRP5) and TT genotype (A1330V LRP5) were associated with lower BMD at the hip, femoral neck, Wards triangle, hands and second proximal phalanges (p <0.001). In the analysis by therapeutic subgroups, these associations remained, particularly at femoral level. The same genotypes were associated with higher sclerostin levels (p <0.001) and lower RANKL (p <0.05). The genotype TT (A1330V polymorphism) was also associated with higher serum OPG (p <0.05). Whether in the subgroup of patients on biologics, whether under classical DMARDs, only the associations with sclerostin levels remained significant. All these associations were found even after adjusting for age, disease duration, body mass index, DAS28 (4v), current HAQ, current average daily dose of prednisolone and years of corticosteroid use. Conclusions: In a rheumatoid arthritis population, the genotypic frequencies of the V667M, N740N and A1330V polymorphisms in LRP5 gene proved to be similar to healthy populations, correlating with femoral and hands bone mass in these patients. The association of these polymorphisms to high serum levels of sclerostin can justify the major lack of bone formation and bone repair in rheumatoid arthritis patients. Disclosure of Interest: None Declared